Patients’ evaluations of patient safety in English general practices: a cross-sectional study - Ricci-Cabello, Ignacio; Marsden, Kate S; Avery, Anthony J.; Bell, Brian; Kadam, Umesh; Reeves, David; Slight, Sarah P.; Perryman, Katherine; Barnett, Jane; Litchfield, Ian; Thomas, Sally; Campbell, Stephen M.; et al. (Royal College of General Practitioners, 2017)
Background: The frequency and nature of safety problems and harm in general practices has previously relied on information supplied by health professionals, and scarce attention has been paid to experiences of patients. Aim: To examine patient-reported experiences and outcomes of patient safety in Primary Care in England. Design and Setting: Cross-sectional study in 45 general practices.